Surveillance of noise exposure levels in workplaces in Beijing - Dong, Yan; Li, Yuqian; Liu, Yan; Zhao, Yan; Zhang, Heng; Sun, Yun; Li, Zizi (Frontiers in Public Health, 2025)
Occupational noise-induced deafness is the second most prevalent occupational disease in China after pneumoconiosis. This study aims to estimate overall noise exposure levels and trends in industrial enterprises in Beijing. A total of 286 enterprises were monitored, and the median and interquartile range (IQR) of noise exposure levels were calculated. The distribution of noise exposure level was analyzed, revealing that 116 enterprises exceeded permissible noise limits. In terms of industry, noise exceedance was observed in 28 enterprises engaged in metal product manufacturing (24.13%) and 27 enterprises in motor vehicle manufacturing (23.28%). Regarding ownership type, 71 limited liability companies exhibited noise exceedance, making up 61.20% of the total. Multivariate logistic regression identified industry-specific risk factors associated with noise exceedance. The risk was significantly higher in metal product manufacturing (OR = 3.31, 95% CI: 1.61–6.82) and railway, shipping, aerospace, and other transportation equipment manufacturing (OR = 12.18, 95% CI: 1.40–105.63). Conversely, enterprises engaged in printing and recorded media reproduction exhibited a lower risk (OR = 0.29, 95% CI: 0.13–0.67). The noise exceedance rate in Beijing is lower than the national average, and levels in line closely with nationwide standards. Detailed surveillance of noise exposure levels provides a basis for occupational health authorities to conduct targeted supervision and formulate industry-specific control measures for high-risk sectors and job roles.